SURGICAL TREATMENT OF IATROGENIC LESION OF TRACHEA USING “COR MATRIX” PATCH - Kondov B; Cholancheski R; Kondov G; Zdravevska M; Spasovska K; Ferati I (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2020)
Injuries of trachea are rare but life-threatening conditions that need urgent and accurate diagnosis and prompt treatment. We present a case of a 29-years old female patient who had two surgical interventions under general anesthesia within a period of four months, in which after the second intervention, subcutaneous emphysema on the neck was detected that was enlarging during the afternoon and therefore an injury of trachea was suspected. CT scan of the neck and thorax was performed that confirmed the subcutaneous emphysema and emphysema in the mediastinum and a suspected lesion of the trachea. Afterword, a bronchoscopy was conducted and a 3 cm long linear lesion of the trachea was visualized 3 cm from the vocal cords and 3,5 cm from the tracheal carina. Then a surgical intervention was performed in general anesthesia, with an approach from the basis of the neck, that led to the dorsal wall of the trachea that was injured, using with PDS suture 000, a part of the lesion was closed, and on the rest part a “cor matrix” patch was placed, which also wrapped the trachea. The patient was extubated the third day after surgery and on the control bronchoscopy the trachea was normal. Early and accurate diagnosis, as well as prompt surgical reparation of tracheal injury provides great morphological and functional results, and prevents further complication.
Keywords: cor matrix; iatrogenic lesion of trachea; surgical treatment